Urgensi Pembinaan Akhlak Bagi Pembangunan Bangsa Perspektif Hasan Al Bana - Ai Rukmini (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2002)
Urgensi Pembinaan Akhlak Bagi Pembangunan Bangsa Perspektif Hasan Al Bana